How Collection Cost Structure Drives a Manufacturer's Reverse Channel Choice. (28th February 2013) - Atasu, Atalay; Toktay, L. Beril; Van Wassenhove, Luk N.
<x xml:space="preserve">Abstract</x> This note discusses the impact of collection cost structure on the optimal reverse channel choice of manufacturers who remanufacture their own products. Using collection cost functions that capture collection rate and collection volume dependency, we show that the optimal reverse channel choice (retailer‐ vs. manufacturer‐managed collection) is driven by how the cost structure moderates the manufacturer's ability to shape the retailer's sales and collection quantity decisions.